A physical rehabilitation of sportsmen is at the osteochondrosis of lumbosacral department of spine on training motive conditions - Пєшкова [Peshkova O.], Ольга Володимирівна; Гончаров [Goncharov A. A.], Олексій Геннадійович (Slobozhanskyi Herald of Science and Sport, 2012)
In the article authors are present these inspections of sportsmen, suffering lumbosacral osteohondrozis. The indexes of the cardiovascular and respiratory system were studied, and also to mobility of lumbosacral department of spine for heavy athletics sportsmen and volley-ballers in sagital, frontal and transversal planes to application of rehabilitation influences. The complex program of physical rehabilitation is worked out for the inspected contingent of sportsmen, which included the elements of traction influence in water in combination with post-isometric relaxation, physiotherapy, psychotherapy and massage on the training motive mode